Peningkatan kesadaran siswa tentang bahaya kecanduan gadget bagi generasi Alpha - Tunjung Bayu Sinta; Noor Lita Sari (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
Gadget addiction among children, particularly those of the Alpha Generation, has become a serious concern due to its negative impacts on physical, mental, and social development. This study aimed to increase students’ awareness of gadget addiction and promote preventive measures. A community service program was conducted at SMP N 3 Mojogedang involving 35 seventh-grade students. The intervention included educational sessions, discussions, and distribution of infographics. Students’ knowledge was assessed using a pretest and posttest design. The findings showed a significant improvement in students’ knowledge: 94.29% of participants achieved a good category after the intervention compared to only 14.29% before. Educational interventions are effective in raising awareness and preventing gadget addiction among Alpha Generation students, highlighting the importance of school-based preventive education.